“Desarrollo de protocolo para la propagación in vitro del phragmipedium kovachii attwood dalstrom & Fernandéz (orchidaceae) a partir de semillas” - Gálvez Panduro, Roger Aly (2005)
The investigation of the present job was done at the Laboratory of Cultivation of Tejidos Vegetales of the a San Martin University of Tarapoto with the objective to evaluate the efficiency of three methods of cultivating in Vitro (germination, multiplication, and rooting) in Phragmipedium kovachii Atwood Dalstrom & Fernandez, to separate seeds for plants free of pathogens and a design was completad at random. 3x10 {methods of cultivating) and 10 repetitions. The seeds in 30 days after the planting in one form of germinating they began to germinate, at 60 days the process of tearing the sprout that covers the embryo for its development and formation of protocormos observing a low level of contamination, after 2 weeks because of the asepsis manner in which it was conducted earlier and during the entire time of chime transplant. At 20 weeks after the planting between the growth {multiply) the plants demostrate average result 3.5 of /eafs and 6.44 mm, high of the plant in the middle M3, in comparison of M13.27 number of leafs and 5.63 mm hígh of plant and M2 with 3.13 number of leafs and 5.24 mm high of plant. At 35 weeks after the planting and in between the rooting of the plants they demostrate average results of 4.3 number of leafs and 7.04 mm high of the plant and in the middle M1; 3.83 number of leafs and 6.62 mm high of the plant in the middle M2 3.5 number of leafs and 6.34 mm high of the plants in the middle of M3. At 40 weeks after the planting and in between the process of rooting, the plants demostrate average results of 0.8 number of roots and 0.61 mm the length of roots, average in the middle M1; 1.01 number of roots average and 0.61 mm the length of roots, average between rooting and 0.54 mm the length of roots average in the M3.